Features of the use of physical exercises at the long-term stage of rehabilitation after intra-articular fractures - Sviatoslava Pashkevych; Tetiana Shutieieva; Оlha Beziazychna (Pedagogy of Health)
Background and Study Aim. The main demand after surgical treatment of the injury is to restore motor function and return to an active lifestyle. The inclusion of effective therapeutic exercises in the rehabilitation program will help to restore the physical activity of patients. The aim of the study is to develop and evaluate the effectiveness of a set of therapeutic exercises to restore the movements of the lower extremities of patients after surgery.